Authoritarian resilience through securitization: an Islamist populist party's co-optation of a secularist far-right party. Issue 6 (18th August 2021) - Yilmaz, Ihsan; Shipoli, Erdoan; Demir, Mustafa
ABSTRACT: This article tackles the puzzle of how Turkey's ruling Islamist populist Justice and Development Party (AKP) was able to co-opt the secularist far-right Nationalist Action Party (MHP) and to ensure the MHP's support in creating an authoritarian regime, despite their previous antagonistic relations and ideological opposition. We investigate this puzzle through the combination of authoritarian resilience/stability theory and securitization theory. The article develops an empirically grounded account of how co-optation has happened in Turkey. In a novel way, it shows that the ruling party's successful securitization of the MHP's antagonists (pro-Kurdish opposition) has facilitated the co-optation of the MHP by the ruling party. This article contributes to the authoritarian stability theory by introducing securitization theory to this literature. It also contributes to the co-optation literature by showing a novel phenomenon: a powerful incumbent party's ideological move towards the smaller to be co-opted party. The article also contributes to the securitization theory debates about the role of securitizing actors and their audiences, as well as the "right" of functional actors in securitizing an issue, despite their initial non-decisive authority.